THE EFFECT OF POLISI RW IMPLEMENTATION IN ACCELERATING SETTLEMENT OF CRIME/ POLICE REPORT: METRO JAYA POLICE DEPARTMENT EXPERIENCE - Dany Rimawan; Lalu Guntur Payasan (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
This study aims to analyze the effectiveness of Polisi RW in accelerating the process of handling crime cases handled in the jurisdiction of the Metro Jaya Regional Police, the reason for choosing the quantitative study is because the concept of Polisi RW has been supported by several concepts, namely Community Policing, Hotspot Policing and Predictive Policing so that quantitative measurements need to be made so that it is clearly visible its effectiveness in certain periods. This study uses quantitative methods with pseudo-experiments, data collection techniques using secondary data on crime handling reports in all areas of the Metro Jaya Resort Police in the January-February 2023 period as pre and as post period March-April 2023. In addition to the difference between the pre and post ranges, researchers also took measurements in the period March-April 2022 with March-April 2023 as comparison data. This study was analyzed using paired sample t-test and cohen's effect size. Test results on differences in the number of crime reports for the period before and after the implementation of RW Police p-value = 0.043, cohen's effect size of 0.541; The number of crime reports for the period March-April 2022 with March- April 2023 found p=value 0.037, Cohen's d= 0.507. There is an influence of RW police on accelerating the process of handling cases and Polisi RW can effectively be used as one of the steps in facilitating case handling in the community, especially Polda Metro Jaya. Re-measurement is required after 6 months of application.